Applications of case study research - Yin, Robert K. (SAGE, 2012)
Designed to help both graduate students and start-up researchers with their own case study research, this book presents 21 individual applications together with cross-referenced discussions of key methodological issues. Many of the applications-including a wide array of single-case studies useful as examples for solo researchers-have been shortened or re-written expressly for this book.